BE INDEPENDENT AND PROVE THAT YOU ARE CAPABLE, USM VC URGES GRADUANDS - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, 26 October 2016 Universiti Sains Malaysia (USM) graduands should be independent especially in creating new job opportunities and not just rely on others.